Book-wheeler - Ghazali, Nor Syahira; Abdullah, Nurani; Mahmood, Mahadi (Universiti Teknologi MARA, Kedah, 2017)
The book-wheeler is designed to minimize the library user effort from carrying books from shelve to another shelve. It will ease the library users from holding books while they browsing another book. This “book-wheeler” also will act as a foldable book rest and will help the library user to read abstract or content of a book before they proceed to borrow or to go to the reading area for further reading. The Book-wheeler is an extended version of the regular book trolley since not only it could help library users from carrying books from shelve to another shelve but it could also act as a foldable book rest to help them to read while browsing books.